Hormonal biomarkers remain prognostically relevant within the molecular subgroups in endometrial cancer - Vrede, Stephanie W; Van Weelden, Willem Jan; Bulten, Johan; Gilks, C Blake; Teerenstra, Steven; Huvila, Jutta; Matias-Guiu, Xavier; Gil-Moreno, Antonio; Asberger, Jasmin; Sweegers, Sanne; van der Putten, Louis J M; Küsters-Vandevelde, Heidi V N; et al. (Gynecologic oncology, 2025)
OBJECTIVE: The prognostic relevance of hormonal biomarkers in endometrial cancer (EC) has been well-established. A refined three-tiered risk model for estrogen receptor (ER)/progesterone receptor (PR) expression was shown to improve prognostication. This has not been evaluated in relation to the molecular subgroups. This study aimed to evaluate the ER/PR expression within the molecular subgroups in EC. METHODS: A retrospective multicenter cohort study was performed and data from the European Network for Individualized Treatment centers and Vancouver, Canada were used. ER/PR immunohistochemical expression was grouped as: ER/PR 0-10 %, 20-80 % or 90-100 %. Molecular subgroups were determined with full next-generation sequencing or combined with immunohistochemistry: POLEmut, mismatch repair deficient (MMRd), p53mut and no-specific molecular profile (NSMP). RESULTS: A total of 739 patients were included (median follow-up 5.0 years). Tumors were classified as POLEmut in 9.1 %(N = 67), MMRd in 27.6 %(N = 204), p53mut in 20.8 %(N = 154) and NSMP in 42.5 %(N = 314). Among all molecular subgroups, patients with ER/PR 90-100 % expression revealed the best disease-specific survival (DSS). Within p53mut, PR 90-100 % expression showed a 5-year DSS of 100.0 %. ER expression is prognostic more relevant in MMRd and NSMP tumors while PR expression in p53mut and NSMP tumors. Across all molecular subgroups, PR 0-10 %, p53mut, lympho-vascular space invasion and FIGO stage III-IV remained independently prognostic for reduced DSS Whereas PR 90-100 % and POLEmut remained independently prognostic for improved DSS. CONCLUSION: We demonstrated that ER/PR expression remain prognostically relevant within the molecular subgroups, and that a three-tiered cutoff refines prognostication. These data support incorporating routine evaluation of ER/PR expression in clinical practice.
Keywords: nádorový supresorový protein p53; senioři; senioři nad 80 let; receptory pro estrogeny; Retrospective Studies; Immunohistochemical; Prognosis; Receptors, Progesterone; Middle Aged; Tumor Suppressor Protein p53; oprava chybného párování bází DNA; Adult; nádory endometria; Endometrial Neoplasms; Biomarkers, Tumor; Aged, 80 and over; ženské pohlaví; nádorové biomarkery; prognóza; DNA Mismatch Repair; retrospektivní studie; Humans; Receptors, Estrogen; Molecular classification; Endometrial carcinoma; lidé středního věku; Pathology; dospělí; Biomarkers; Female; Aged; lidé; receptory progesteronu